Output Price Risk, Material Input Price Risk, and Price Margins: Evidence from the US Catfish Industry. - David Bouras; Ogugua Anunoby; Otabek Saitakhunov (Journal of Economics and Management, 2017)
Aim/purpose - To develop a conceptual model for analyzing the impact of output price risk and material input price risk on price margins. Design/methodology/approach - To analyze the combined effect of output price risk and material input risk on price margins, we use a series of comparative static analyses, GARCH models, and data ranging from 1990/01 to 2012/12. Findings - The theoretical results indicate that the impact of output price risk and the impact of material input price risk on price margins are ambiguous and, to a great extent, hinge on the correlation between output price and material input price. The empirical results show that whole frozen catfish price risk and live catfish price risk negatively affect the price margin for frozen catfish. The empirical results, however, indicate that the risk of the price of live catfish affects markedly the price margin for frozen whole catfish in contrast to the impact of the risk of the price of frozen whole catfish. Research implications/limitations - The empirical results have significant implications for managerial decision-making especially when crafting strategies for improving price margins. Accordingly, in order to beef up the price margin for frozen whole catfish, catfish processors may consider engaging in vertical integration. This paper has some limitations: first, it assumes that firms operate in competitive markets; second, it assumes that firms produce and sell a single product. Originality/value/contribution - Unlike earlier studies that focused solely on the effect of output price risk on price margins, this paper analyzes theoretically and empirically the impact of output price risk and material input price risk on price margins.